A Feasibility Study on the Establishment of Cold Cuts Veggie Longganisa in Home Base Residence (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
A healthier variety of Veggie Longganisa are what we are in cognizance. For this brand perception that we formalize we would like to linger the interest of the buyers and also the consumer with our version of Veggie Longganisa. This product is called “Veggie Longganisa” Nutri Veggie is the name of the food stall where it will be sold to costumer. The primary concept of the business is to produce quality vegetable Longganisa that are healthy, tasty and affordable. Nowadays people would choose an artificially made food product that has less healthy nutritional content over the conventional food that is said to be “good for our health” that is available in the market. Promoting a healthy and convenient way of eating by introducing varieties of Veggie Longganisa to the public consumers would also benefit with its health nutrition content, it also helps the Filipino farming industries in the country as well. The researcher use survey method because we believe that the use of survey method will help the researchers get the respondent perception to the product easily. Using the survey method they analayze the demand quantity of each product and project the product if it effective or not. The respondent considers the factors in marketing aspects of the business such as product pricing strategy place and promotion. The result of our survey is successful. 75% of the respondents are female and 25% are male who agreed that our product is acceptable to our community because of its uniqueness and a healthier variety of new Veggie Longganisa in Sauyo, Novaliches Quezon City. The business is focused on the feasibility study of veggie longganisa in Sauyo, Novaliches Quezon City, that offers a new blend of longganisa. Nowadays, people would choose an artificial made food product that has a less healthy and nutritional content over the conventional foods that is good for our health and that is available in the market or online. Based on the research and study that we conducted, we therefore conclude that our business will be successful.
Keywords: cold cuts veggie longganisa, feasibility study, BCP